2020
DOI: 10.1021/acsami.0c15114
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of Rubber with Nano ZnO as Activators

Abstract: The vulcanization of rubber is a chemical process to improve the mechanical properties by cross-linking unsaturated polymer chains. Zinc oxide (ZnO) acts as an activator, boosting the rubbers’ sulfur vulcanization. Maintaining the level of ZnO content in the rubber compounds as low as possible is desirable, not only for economic reasons but also to reduce the environmental footprint of the process. In this contribution, octylamine (OA) capped ZnO nanoparticles (5 nm diameter), prepared through a thermal decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…This is because the interaction of hybrid fillers with accelerator CZ and activator ZnO promote their dispersion in rubber matrix and accelerate the rapid formation of sulfur bonds between rubber molecular chains. 33 1# has the largest optimum cure time (t c90 ), which is because the agglomeration of SiO 2 causes uneven dispersion in the composite material. 34…”
Section: Rheology Performance Of Esbr/ Nrl Compositesmentioning
confidence: 99%
“…This is because the interaction of hybrid fillers with accelerator CZ and activator ZnO promote their dispersion in rubber matrix and accelerate the rapid formation of sulfur bonds between rubber molecular chains. 33 1# has the largest optimum cure time (t c90 ), which is because the agglomeration of SiO 2 causes uneven dispersion in the composite material. 34…”
Section: Rheology Performance Of Esbr/ Nrl Compositesmentioning
confidence: 99%
“…198 A recent research demonstrated the usage of 5-nm OA-capped ZnO nanoparticles in the vulcanization of natural rubbers. 199 Compared to commercialized ZnO, OA-capped nanosized ZnO exhibited significantly better dispersion in a rubber matrix and effectively improved the curing efficiency of natural rubber, which potentially could have a great impact on reducing ZnO loadings in commercial rubber manufacturing. Also, ZnO has been increasingly applied in the area of photocatalysis, because of its prominent photocatalytic activity.…”
Section: (Scheme 5)mentioning
confidence: 99%
“…ZnO plays an important role in promoting the formation of sulfide cross-links and improving the kinetics of the curing process, thus achieving higher cross-linking densities in rubbers . A recent research demonstrated the usage of 5-nm OA-capped ZnO nanoparticles in the vulcanization of natural rubbers . Compared to commercialized ZnO, OA-capped nanosized ZnO exhibited significantly better dispersion in a rubber matrix and effectively improved the curing efficiency of natural rubber, which potentially could have a great impact on reducing ZnO loadings in commercial rubber manufacturing.…”
Section: Applications Of Zno/polymer Hybrid Materialsmentioning
confidence: 99%
“…Nowadays, the reduction of ZnO content in rubber products can be achieved through various methods, that is, (1) the utilization of nanosized ZnO, [33][34][35][36] (2) the replacement of ZnO with zinc-based curing agents, [37][38][39][40][41] and (3) the synthesis and usage of composite ZnO produced by depositing ZnO on various supporting cores. [42][43][44][45][46][47] The last one seems to be a promising method to effectively reduce the composition of ZnO and produce the more eco-friendly material.…”
Section: Introductionmentioning
confidence: 99%